2008
DOI: 10.1016/j.juro.2007.08.087
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Expression Pattern of ErbB Family Receptors Signifies an Aggressive Variant of Bladder Cancer

Abstract: Purpose-Expression of various members of the ErbB family (EGFR/ErbB-1, ErbB-2, ErbB-3, and ErbB-4) has been associated with stage of disease and survival in patients with urothelial carcinoma (UC). We examined the correlation of expression of ErbB family receptors with progression of UC, and survival.Methods-A UC tissue array was constructed from 248 archival paraffin blocks, and quality control studies were ascertained. The tissue microarray was stained for EGFR, ErbB-2, ErbB-3, and ErbB-4, and was analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 16 publications
1
78
0
Order By: Relevance
“…It also pointed out that HER2 status in BC varies from 9% to over 80% in regards to protein overexpression and 0-32% regarding gene amplification (4-76 and 3-9% in NMIBC, respectively, in Table 1); furthermore, conflicting data exist regarding its prognostic relevance in BC [18,24,[26][27][28][29][30][31][32][33][34][35][36]. The reason for such variability of HER2 positivity is multifactorial, resulting from (a) tumor heterogeneity, with case series featuring varying tumor stages and histological grades (and different grading systems), (b) the diversity of methods used to assess HER status (amplification detection versus overexpression detection), (c) the technique used (polymerase chain reaction [PCR], in situ hybridization [ISH] and immunohistochemistry [IHC]) to assess HER2 status, and also (d) the specific definition given to HER2 "positivity" [24,37,38]; ethnic or geographic differences may account for further reasons [39].…”
Section: Her2 and Bcmentioning
confidence: 99%
See 1 more Smart Citation
“…It also pointed out that HER2 status in BC varies from 9% to over 80% in regards to protein overexpression and 0-32% regarding gene amplification (4-76 and 3-9% in NMIBC, respectively, in Table 1); furthermore, conflicting data exist regarding its prognostic relevance in BC [18,24,[26][27][28][29][30][31][32][33][34][35][36]. The reason for such variability of HER2 positivity is multifactorial, resulting from (a) tumor heterogeneity, with case series featuring varying tumor stages and histological grades (and different grading systems), (b) the diversity of methods used to assess HER status (amplification detection versus overexpression detection), (c) the technique used (polymerase chain reaction [PCR], in situ hybridization [ISH] and immunohistochemistry [IHC]) to assess HER2 status, and also (d) the specific definition given to HER2 "positivity" [24,37,38]; ethnic or geographic differences may account for further reasons [39].…”
Section: Her2 and Bcmentioning
confidence: 99%
“…On the other hand, Gandour-Edwards et al [31] reported an increased DSS in patients who overexpressed HER2 when treated with paclitaxel-based CT for advanced BC. Finally, some other studies failed to detect any correlation between HER2 status and survival outcomes [36,47,69,84].…”
Section: Survival Outcomesmentioning
confidence: 99%
“…14 Tumor invasion and histologic grade were classified according to the TNM staging and the 1997 World Health Organization grading system, respectively. 15 The tumors were grouped based on stage into noninvasive (Ta-T1a) and invasive (T1b-T4) as described previously. 16 The patient population studied consisted of 34 cases of noninvasive low-grade (grade 1-grade 2) papillary tumors, 9 cases of noninvasive highgrade (grade 3) papillary tumors, 13 cases of invasive high-grade (grade 3) papillary tumors, and 89 cases of invasive high-grade (grade 3) nonpapillary tumors.…”
Section: Patients and Tissue Samplesmentioning
confidence: 99%
“…Overexpression of EGFR, and amplification/overexpression of ERBB2 is more common in muscle-invasive tumors, but their prognostic significance is controversial [57]. Agents with EGFR, HER-2, and mixed pharmacologies have all entered clinical trials in bladder cancer patients.…”
Section: Targeting Growth Factor Receptors and Signal Transduction Pamentioning
confidence: 99%